Prognostic value of coronary artery calcium score in hospitalized COVID-19 patients. (14th October 2021) - Motoc, A; Luchian, M L; Lochy, S; Belsack, D; Magne, J; Roosens, B; De Mey, J; Boeckstaens, S; Van Den Bussche, K; Von Kemp, B; Galloo, X; Francois, C; et al.
Abstract: Background: The association between known cardiovascular risk factors and poor prognosis of patients diagnosed with coronavirus disease 2019 (COVID-19) has been recently emphasized (1). Coronary artery calcium (CAC) score assessed by computed tomography (CT) is considered a risk modifier in primary prevention of cardiovascular disease and has shown to improve cardiovascular risk prediction in addition to classical risk factors (2). Purpose: We hypothesized that the absence of CAC might have an additional predictive value for an improved cardiovascular outcome of hospitalized COVID-19 patients. Methods: We prospectively included 310 consecutive hospitalized patients with COVID-19. Thirty patients with a history of coronary artery disease were excluded.Low dose non-contrast chest CT was performed in all patients at admission. Visual assessment of CAC in every coronary artery was obtained by using an ordinal scoring of 0, 1, 2 or 3 corresponding to absent, mild, moderate or severe CAC score. A total score was calculated by summing the score of each vessel, which was further categorized as 0 (undetectable), 1–3 (mild), 4–5 (moderate) and ≥6 (severe). (Figure 1). Demographics, medical history, clinical characteristics, laboratory findings, imaging data, in–hospital treatment and outcomes were retrospectively analyzed. A composite endpoint of major adverse cardiovascular events (MACE) was defined as all-cause mortality and cardiovascular events (heart failure, myocarditis, arrhythmia, acute coronary syndrome, stroke, pulmonary embolism). Results: Two-hundred eighty patients (63.2±16.7 years old, 57.5% male) were included in the analysis. One hundred thirty one (46.7%) patients had a CAC score of zero. MACE-rate was 24.2% (68 patients). Multivariate logistic regression showed that the absence of CAC was inversely associated with MACE (OR 0.264, 95% 0.071–0.981, p=0.047), with a negative predictive value (NPV) of 81.4%, sensitivity 70%, specificity 55%, independent of age, risk factors or disease severity (Table 1). Conclusion: The absence of CAC translated into a low risk for MACE in COVID-19 patients, even in the presence of cardiac risk factors, which reinforces the idea that the assessment of CAC score in COVID-19 patients could be a useful marker for patients risk stratification and management. Future directions should focus on the implementation of CAC score into mid-term and long-term follow-up of this particular population, to provide a more precise and earlier estimation of cardiovascular risk Funding Acknowledgement: Type of funding sources: None.